Socioemotional wealth and family commitment - Razzak, Mohammad Rezaur; Abu Bakar, Raida; Mustamil, Norizah (Emerald, 2019)
Purpose: The purpose of this paper is to determine the elements of family-centric non-economic goals, such as socioemotional wealth (SEW) of family business owners, that drive family commitment. The empirical study further tests whether such relationships are impacted by the aspect of ownership, that is, who controls the firm: founder generation or subsequent generation of owner managers. Design/methodology/approach: Deploying the SEW and stakeholder theories, this study proposes a conceptual link between soecioemotional wealth dimensions and family commitment. The study is based on a survey of 357 private family firms in Bangladesh involved in manufacturing ready-made garments. The respondents are all in senior-level management positions in their respective firms and are members of the dominant owning family. Findings: Prior to considering the moderating effect of controlling generation, the results indicate that four out of five FIBER dimensions of SEW affect family commitment, except for binding social ties. The study also finds that when a comparison is made between the founder generation and the subsequent generation of family firm managers, it is the latter that manifests significantly higher levels of family commitment when the focus is on the two FIBER dimensions of SEW: binding social ties and identification of family members with the firm. Research limitations/implications: Although the cross-sectional nature of the study exposes the study to the specter of common method bias, procedural remedies were initiated to minimize the likelihood. Furthermore, data were collected from a single key informant in each organization. Therefore, both a longitudinal study and corroborating data from more than one individual in each firm would possibly provide a more robust picture. Practical implications: Key decision makers from within the family who wish to see their subsequent generation remain engaged and committed to the family firm may find cues from the fact that focusing on binding social ties and identification of family members with the firm play an important role in ensuring continued commitment to the business by their successors. Social implications: Family businesses are recognized to be vital contributors to most societies around the globe, both as employment generators as well as catalysts of economic activities. Hence, policy makers may derive pertinent information from the study in adopting policies to nurture and ensure survival and continuity of family-owned businesses, by understanding how family-centric non-economic goals impact family’s desire to commit resources, time and effort to the enterprise from generation to generation. Originality/value: Determining the factors that drive continued engagement and commitment of family members to the business enterprise is a phenomenon that needs to be better understood in order to ensure continuity and survival of family enterprises across generations. This study attempts to provide a more nuanced understanding of how different components of family-centric goals, such as SEW, impact family commitment. The study contributes to theory building by providing a conceptual link that demonstrates the components of SEW that are most pertinent in terms of ensuring higher levels of family commitment to the family-owned business. © 2019, Emerald Publishing Limited.